Analisis Strategi Pemasaran Tembakau Reconsitute (Studi Kasus di PT. Natobin Tobacco Internasional, Bondowoso) - Gozi, Ahmad; Suharto, Akhmad; Izzuddin, Ahmad (IPM2KPE, 2024)
This study aims to analyze the marketing strategy related to PT. Natobin Tobacco Internasional in marketing recon tobacco in competition with pure tobacco in cigarette factories in Indonesia. As well as to determine the supporting and inhibiting factors of the marketing strategy at PT. Natobin Tobacco International. This type of research is descriptive. The population in this study are company owners and employees at PT. Natobin Tobacco International, with the sampling technique using purposive sampling method. Data was collected by questionnaire and analyzed by SWOT. The results of the research show that the main factor that becomes the strength of PT. Natobin Tobacco International has a wide distribution network with a large number of 0.60. The main weakness of the company based on the calculation of the IFAS Matrix is related to the increase in production costs which can affect company profits with a score of 0.32. PT. Natobin Tobacco Internasional is a company that can expand its market overseas with a score of 0.57, while PT. Natobin Tobacco International is competition with other tobacco companies that will emerge in the future, for example, large companies have started to get involved in tobacco, with a score of 0.33. The right alternative strategy to be implemented by PT. Natobin Tobacco International is a strategy of product differentiation and brand strengthening can help companies maintain market share and increase competitive advantage. Keywords: Keywords: Natobin Tobacco International, SWOT, Reconstituted Tobacco